MODEL ANTREAN NORMAL DAN TRIANGULAR (Studi Kasus : Gerbang Tol Tembalang Semarang) - Sugito Sugito (MEDIA STATISTIKA, 2017)
The growing number of vehicle in each year resulting an inevitable congestion, one of them is jamming vehicle transaction in Tembalang toll gate. This condition can cause dissatisfaction to the toll road users in obtaining services. It is need to be specified the appropriate queue system model to the conditions of service in Tembalang toll gate. So it can be determined the number of booth service is working optimally. Based on the data analysis obtained from the Arena software, the queue system model that can describe the conditions of service at Tembalang toll gates with data total- time, time-total, and time-time the direction of Srondol-Jatingaleh at the regular toll booth is (Norm/G/2):(GD/∞/∞), (G/Norm/2): (GD/∞/∞), (G/G/2): (GD/∞/∞) and at the automatic toll booth is (G/Tria/3): (GD/∞/∞), (Tria/G/3): (GD/∞/∞), (G/G/3): (GD/∞/∞) while with the direction of Jatingaleh-Srondol at the regular toll booth is (Norm/G/3): (GD/∞/∞), (G/Norm/3): (GD/∞/∞), (G/G/3): (GD/∞/∞) and (G/Tria/2): (GD/∞/∞),  (Tria/G/2): (GD/∞/∞), (G/G/2): (GD/∞/∞) at automatic toll booth.